Aspectos geológicos y geomorfológicos del sector N del golfo San Matías, Río Negro, Argentina - Fucks, Enrique (2012)
The geological-geomorphological features of the San Matías Gulf suggest its genesis was associated with deflation processes, to which periodically added littoral processes related to transgressions. On the northern margin, four transgressive cycles have been recognized, three of the Pleistocene and one of the Holocene. The oldest transgression is scarcely represented, and was recognized between heights 60 to 70 m. The MIS 7 transgression is at the sea level and corresponds to the Baliza San Matías Formation, with the development of extended conglomerate exposures as coastal plains. The MIS 5e deposits are the best represented, with uniform morphologies at 15 m height. These deposits were defined as the San Antonio Formation, Holocene in age. The ingression of the MIS 1 is little developed, only as a fringe parallel to the coast in low or easily eroded sectors, about 5-6 m height. The 15 m height for the MIS 5e is thought to correspond to macrotidal characteristics of the area, suggesting that this is an important factor to bear in mind when considering the height of the transgressive deposits and their relationships with sea level. The little significance of the Holocene deposits has caused the stratigraphic confusion in the area. These latter deposits have not been named, instead the MIS 7 and MIS 5e correspond to the Baliza San Matías and San Antonio Formations respectively